Changes in stature of Portuguese women born between 1966 and 1982, according to educational level - Cardoso, Hugo F. V. (2012)
Studies which document secular change in stature are almost exclusively based on males, while similar data on females is less common. In addition, secular trends in socioeconomic differences of height are seldomly reported. This study aims to document changes in mean stature in a sample of Portuguese women born between 1966 and 1982 (n = 30,629). For this study self-reported stature data was obtained from a large sample of women who delivered their children at the Dr. Alfredo da Costa Maternity Hospital, in Lisbon, between 1991 and 2004. Reported data on educational level was used as a proxy for socioeconomic status to assess changes in female stature in relation to their social class. Results show that female stature in the sample increases during the time period considered (mean stature: 160.8 cm in 1966 and 161.1 cm in 1982), but not consistently. In addition, women of higher educational level are systematically taller than their lower educational level counterparts (mean stature difference between highest and lowest educational level groups is 4.2 cm). Compared to males, mean stature increase in females was about 75% less. Although the time period considered is short, this study documents important socioeconomic differences in female stature and is the first to report stature changes over time in Portuguese women.